A randomized clinical trial testing a health literacy intervention to reduce disparities in access to care among Justice-Impacted Adults (JIA) - Victoria D. Ojeda; Arthur Groneman; Sarah Hiller-Venegas; Melissa Moreno; Briana Schuler; Jerrica Barksdale; Emily Berliant; Natalie Romero; Todd M. Edwards; Zephon Lister; Todd Gilmer; Tommi Gaines; et al. (BMC, 2024)
Abstract Background Low health literacy is costly and observed among justice-impacted adults (JIA), a group that often faces numerous barriers in accessing healthcare and a disproportionate burden of illness. Health literacy interventions for JIA are critically needed to improve healthcare access and related outcomes. Methods This manuscript describes the protocol for a longitudinal mixed-methods randomized clinical trial that assesses the effectiveness of a coach-guided health literacy intervention on JIA's healthcare access. The intervention was previously piloted with justice impacted adults. We will recruit 300 JIA ages 18 + in San Diego, California. Participants will be randomized 1:1 to the Treatment Group (i.e., coach-guided intervention providing 12 sessions of individualized health coaching and service navigation over 6 months) or the Control Group (i.e., self-study of the health coaching program, and brief service navigation support). We will quantitatively assess JIA's healthcare access defined as: use of healthcare, health insurance status, and regular source of care at 6-months as the primary outcomes. Participants will also be surveyed at 12-months. Statistical analyses will incorporate the intent-to-treat (ITT) principle and we will estimate mixed-effects logistic regression for the primary outcomes. We will also conduct qualitative interviews at 6 and 12-months with 40 purposively sampled participants, stratified by study arm, who reported healthcare access barriers at baseline. Interviews will explore participants' satisfaction with the intervention, healthcare attitudes, self-efficacy for and barriers to healthcare access over time, perceived contribution of the intervention to health and well-being, and diffusion of intervention-related information within participants' social networks. We will conduct deductive thematic analyses of qualitative data. Discussion Low health literacy among JIA is a foundational challenge requiring tailored intervention strategies. Findings from this trial may inform policies and the structure of service delivery models to build health literacy among JIA in institutional and community settings throughout the United States and elsewhere. Trial registration This study is registered with the United States' ClinicalTrials.gov registry under protocol # 161,903.